FARMERS' RESPONSE TO CLIMATE CHANGE IN LEBAK BUDI VILLAGE, WEST MERAPI SUBDISTRICT, LAHAT REGENCY, SOUTH SUMATRA PROVINCE - Heripan Heripan; Delfy Lensari; Nena Waloka (Universitas Muhammadiyah Palembang, 2026)
Indonesia possesses abundant natural resources, yet high levels of environmental degradation are believed to contribute to climate change, which brings rising sea surface temperatures, extreme weather intensity, and shifting rainfall patterns with sustained consequences for farmers' livelihoods. These impacts can be mitigated if farmers possess adequate knowledge to shape their perceptions and undertake appropriate adaptation measures. This study aims to analyze farmers' knowledge, perceptions, and adaptation strategies regarding climate change in Lebak Budi Village, West Merapi Subdistrict, Lahat Regency. The study employed a descriptive qualitative and quantitative method, with a census sample of 65 farmers affected by climate change. Data were analyzed using descriptive tabulation for knowledge, a Likert scale for perception, and narrative description for adaptation. Results showed that farmers' knowledge of climate change was high (98%), while perception fell into the